Kajian Publik Terhadap Pelayanan Pembuatan KTP Elektronik Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Mojokerto - Hikmah Muhaimin; Desi Nur V; Nasihul Amin; Zelga Navy A. P; Azzara Rum; M. Ghozali (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2022)
A national population database that has a security or control system both in terms of administration and information technology is the basis of the document known as E-KTP or Electronic KTP. It serves to identify Indonesian citizens using this identity card. In February 2011, the Indonesian Ministry of Home Affairs introduced the Electronic KTP or E-KTP program. With E-KTP, all database-based administrative security systems are included in this government initiative for data collection. The KTP is expected to have access to the NIK which is used for daily population administration matters. E-KTP is used to identify Indonesian residents. The E-KTP issue in Indonesia is a significant and complicated issue, and many strategies or tactics have been used by the government to address it so far. The Indonesian government uses the role in the implementation of E-KTP as one of the methods or strategies to attract public attention. The study aims to provide more individualized and high-quality services to each resident while facilitating efficient administration. The underdeveloped population of Mojokerto district was also targeted by this initiative, which also sought to promote accurate data, improve quality, and streamline services. In addition to options, improving HR (Human Resources) or worker capacity to supply various service management-related resources accessible through structured training at various levels is another way to improve service quality. The Mojokerto District Population and Civil Registration Office's E-KTP service has been subjected to community feedback as part of the qualitative study approach. The results show that the community's evaluation of the Mojokerto District Population and Civil Registration Office's services in making E-KTP can be seen from the ease of the service process, and the service still needs to be improved.